Hydroxychloroquine as a primary prophylactic agent against SARS-CoV-2 infection: A cohort study. (July 2021) - Kamstrup, Peter; Sivapalan, Pradeesh; Eklöf, Josefin; Hoyer, Nils; Ulrik, Charlotte Suppli; Pedersen, Lars; Lapperre, Therese S.; Harboe, Zitta Barrella; Bodtger, Uffe; Bojesen, Rasmus Dahlin; Håkansson, Kjell E.J.; Tidemandsen, Casper; et al.
Highlights: Largest cohort study on hydroxychloroquine prophylaxis for coronavirus disease 2019 to date. Included all users of hydroxychloroquine in Denmark before the pandemic. Hydroxychloroquine does not alter the risk of severe acute respiratory syndrome coronavirus-2. Abstract: Objective: Hydroxychloroquine has been proposed as a primary prophylactic agent against coronavirus disease 2019 (COVID-19). This study aimed to investigate if patients treated with hydroxychloroquine for a non-COVID-19 indication had a lower risk of verified infection with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) compared with matched controls. Methods: A cohort comprising all persons in Denmark collecting hydroxychloroquine prescriptions in 2020 and 2019 (i.e., both during and before SARS-CoV-2 was confirmed in Denmark), matched by age and sex with controls, was studied. Data were collected using the Danish national registries, which contain complete information on patient health data, prescriptions and microbiological test results. The main outcome was microbiologically verified SARS-CoV-2 infection. Results: In total, 5488 hydroxychloroquine users were matched with 54, 486 non-users. At baseline, the groups differed in terms of diagnoses of pulmonary disease, cardiovascular disease, renal disease, gastrointestinal/metabolic disease and dementia, as well as treatment with antirheumatic drugs. The final model was adjusted for these potential confounders. Use of hydroxychloroquine for non-COVID-19 indications was not associated with any change in confirmed SARS-CoV-2 (hazard ratio 0.90, 95% confidence interval 0.76–1.07). This result was robust in the propensity-score-matched sensitivity analysis. Conclusion: This study, which is the largest to date to investigate the primary prophylactic effect of hydroxychloroquine against SARS-CoV-2, does not support any prophylactic benefit of hydroxychloroquine in the prevention of infection with SARS-CoV-2.